From Waste to Value: Eco-Enzyme as a Multifunctional Natural Liquid — A Community Service Initiative - Lida Amalia; Sri Mulyaningsih; Rifaatul Muthmainnah; Tati Kristianti; De Budi Irwan Taopik (Fakultas Kewirausahaan Universitas Garut, 2026)
Eco-enzyme is a complex liquid produced through the fermentation of organic waste such as fruit and vegetable peels, commonly prepared using a 1:3:10 ratio of sugar, organic waste, and water. Due to its various practical benefits in daily life, public awareness and understanding of eco-enzyme production need to be improved through community service activities. This community engagement program aimed to enhance community knowledge and skills in converting organic household waste into eco-enzyme. The program involved preparation, educational sessions, concept introduction, workshops, and hands-on practice, supported by PowerPoint presentations and videos. Participants consisted of 30 residents of Parakan Village, Samarang District, Garut Regency, including household heads, housewives, and village youth. Participant responses were collected through questionnaires and analyzed descriptively. The activity was successfully implemented, as reflected by participants’ enthusiasm and overwhelmingly positive feedback regarding its usefulness and applicability at home. Ekoenzim merupakan larutan kompleks yang dihasilkan dari fermentasi limbah organik, seperti kulit buah dan sayur. Larutan ini dibuat dari campuran gula, kulit buah/sayur, dan air dengan perbandingan umum 1:3:10. Ekoenzim memiliki berbagai manfaat dalam kehidupan sehari-hari sehingga perlu disosialisasikan kepada masyarakat. Salah satu upaya yang dapat dilakukan adalah melalui kegiatan Pengabdian kepada Masyarakat (PKM). Kegiatan ini bertujuan meningkatkan pengetahuan dan keterampilan masyarakat dalam mengolah sampah organik menjadi ekoenzim. Metode yang digunakan meliputi tahap persiapan, edukasi dan pengenalan konsep, workshop, serta praktik langsung pembuatan ekoenzim. Penyampaian materi dilakukan menggunakan media PowerPoint dan video. Peserta kegiatan berjumlah 30 orang yang terdiri atas kepala keluarga, ibu rumah tangga, dan pemuda Desa Parakan, Kecamatan Samarang, Kabupaten Garut. Respon peserta diperoleh melalui kuesioner dan dianalisis secara deskriptif kualitatif. Kegiatan PKM berjalan dengan baik dan lancar, ditunjukkan oleh antusiasme peserta serta hasil kuesioner yang menunjukkan respon positif sebesar 100%.